Tibetan Sheep Adapt to Plant Phenology in Alpine Meadows by Changing Rumen Microbial Community Structure and Function - Liu, Hongjin; Hu, Linyong; Han, Xueping; Zhao, Na; Xu, Tianwei; Ma, Li; Wang, Xungang; Zhang, Xiaoling; Kang, Shengping; Zhao, Xinquan; Xu, Shixiao (Frontiers in Microbiology, 2020)
The rumen microbiota is strongly associated with host health, nutrient absorption, and adaptability. However, the composition, functioning and adaptability of rumen microbiota in Tibetan sheep across different phenological periods are unclear. In this study we used sequencing of the V4-V5 region of 16S rRNA, qPCR technology and metagenomics to investigate the adaption of rumen microbiota to forage in different stages of phenology. In a grassy period, due to the high nutritional quality of the forage, Tibetan sheep can produce high concentrations of NH3-N and short fatty acids by increasing the content of key bacteria in the rumen, such as Bacteroidetes, Prevotella, Succiniclasticum, Treponema, Butyrivibrio fibrisolvens, Firbrobacter succinogenes, Prevotella ruminicola, Rumincoccus albus and Rumincoccus flavefaciens to aid in growth. In the withering period, there was a positive correlation between microorganisms which indicated the closely cooperation between microorganisms, and metagenomic analysis showed that the high genes (GHs and CBMs) and subtribe (GH8, GH12, GH45, GH6, GH9, GH5, GH10, GH3, GH52, GH11, GH57, CBM1, CBM4, CBM6, CBM16, CBM37, CBM13, CBM35, CBM42, CBM32 and CBM62) that encode cellulolytic enzymes were significantly increased when the host faced low quantity and quality of forage. Genes involved in metabolic pathways, fatty acid biosynthesis and biosynthesis of antibiotics were significantly enriched, which indicated that rumen microbiota could improve plant biomass deconstruction and energy maintenance in the face of nutritional deficiencies. In the regreen period, both the composition and function of rumen microbiota had obvious disadvantages, therefore, to improve the competitiveness of microorganisms, we suggest Tibetan sheep should be supplemented with high-protein feed. This study is of great significance for exploring the high altitude adaptability of Tibetan sheep.